Proximal margin length with transhiatal gastrectomy for Siewert type II and III adenocarcinomas of the oesophagogastric junction. Issue 8 (10th June 2013) - Mine, S.; Sano, T.; Hiki, N.; Yamada, K.; Kosuga, T.; Nunobe, S.; Yamaguchi, T.
<x xml:space="preserve">Abstract</x> Background A gross proximal oesophageal margin greater than 5 cm is considered to be necessary for curative surgery of adenocarcinoma of the oesophagogastric junction. This study investigated whether a shorter proximal margin might suffice in the context of total gastrectomy for Siewert type II and III tumours. Methods The gross proximal margin was measured on stretched specimens just after resection. Relationships between gross proximal margin lengths and clinicopathological features were investigated in patients with Siewert type II and III adenocarcinoma of the oesophagogastric junction treated by R0–1 surgical resection. For survival analyses, only patients who had undergone R0 resection for pathological (p) T2–4 N0–3 M0 tumour via a transhiatal approach were evaluated. Results Of the 140 patients, 120 had a total gastrectomy. Two patients (1·4 per cent) had histologically positive proximal margins and another two (1·4 per cent) developed anastomotic recurrence. Of 100 patients with pT2–4 N0–3 M0 tumours who underwent gastrectomy via a transhiatal approach, those with gross proximal margins larger than 20 mm appeared to have better survival than those with shorter margins (P = 0·027). Multivariable analysis demonstrated that a gross proximal margin of 20 mm or less was an independent prognostic factor (hazard ratio (HR) 3·56, 95 per cent confidence interval 1·39 to 9·14; P = 0·008), as was pathological node status (HR 1·76, 1·08 to 2·86; P = 0·024). Conclusion Gross proximal margin lengths of more than 20 mm in resected specimens seem satisfactory for patients with type II and III adenocarcinoma of the oesophagogastric junction treated by transhiatal gastrectomy.